Mediating Elderly-Friendly Hajj: An Analysis of the Ministry of Religious Affairs’ Socialization Strategy in Indonesia, 2023–2024 - Yuningsih, Yuyun; Fakhruroji, Moch; Setiawan, Asep Iwan (Hanifiya: Jurnal Studi Agama-Agama, 2026)
The significant growth in the number of elderly Hajj pilgrims in Indonesia has prompted the need for inclusive policies that focus not only on technical aspects but also on the formation of fair and humane public perceptions of this vulnerable group. This study aims to describe the construction of the Elderly-Friendly Hajj program in the media of the Indonesian Ministry of Religious Affairs in 2023–2024, identify key messages, and analyze the context of media use in program socialization. The study uses a constructivist paradigm with a qualitative case study approach, through documentation of the official social media of the Indonesian Ministry of Religious Affairs, in-depth interviews with officials and communication practitioners, and analyzed using the interactive model of Miles and Huberman. The results show that the media constructs the elderly as active subjects with spiritual capacity and an important role in worship, emphasizing humanistic, inclusive, and humanitarian-value-based Hajj services. Media messages are effective, encouraging active participation, highlighting special facilities, physical and mental readiness, mentoring, health education, elderly-friendly worship, and the digitalisation of services. The use of media is participatory and empathetic, becoming a space for education, advocacy, and the formation of public opinion based on multi-platform technology. This study presents a social media construction-based policy communication model that integrates message values, digital technology, and inclusive public policy.